From Friends to Enemies? The Euro as a Cause of New Nationalism - Charles B. Blankart (Center for Economic Studies and ifo Institute (CESifo), 2014)
It is often disregarded that the euro is first of all a public good based on common institutions such the European Central Bank, the Governing Council and a network for executing transactions etc. Establishing a public good is fundamentally different from trade in private goods. A public good needs a coordinated action. All participants have to join their efforts towards the same goal. The more one individual contributes to the public good, the less has to be contributed by the other individuals which is an invitation to free riding. This is an inherent weakness of a public good as compared to private goods. If the partners are badly chosen in the beginning or if they shirk on their contribution, the public good is not produced or it is badly produced and ends in a crisis. No repair is possible. The venture has to be started anew.
Keywords: G00; H00; 330